BENTUK PENGELOLAAN PANTAI BATU BOLONG SEBAGAI DAYA TARIK WISATA SURFING DI DESA CANGGU, KECAMATAN KUTA UTARA, KABUPATEN BADUNG - Ni Komang Permilasari; I Nyoman Sukma Arida (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2014)
Abstract Canggu village now has developed into a tourist area visited by many domestic and foreign tourists because of the potential of nature, especially the potential of beach owned by the village of Canggu. One of the many beaches visited is Batu Bolong which used as a place to learn surfing. Many tourists who visit for surfing activities on the beach making communities build supporting facilities of tourism activities in Batu Bolong Beach, for it was in this study, researchers wanted to know the potential of tourism and the type of management in Batu Bolong Beach as a tourist attraction surf by dividing it into two potential indicators of the potential physical and non-physical that is institutional or organizational, human resources and culture. While for its management, is divided into two indicators of potential management and facilities management are available in Batu Bolong Beach. Batu Bolong beach used as a place to learn to surf (surfing) by tourists, especially foreign tourists because it has the waves are not too big so it is suitable for surfers (surfers) beginner. While the potential for coastal management there has been no specific organization that handles, managing only limited security, hygiene and board rentals in Batu Bolong Beach is managed by two organizations and form a group in the field of rental board. In addition, for the management of the facilities available today is managed by many of these temples which consists of three hamlets.